PENGARUH LATIHAN BARIER HOPS TERHADAP POWER OTOT TUNGKAI PADA TIM BOLAVOLI SMAN 1 SUNGAI MANDAU - Hotliwanto, Hotliwanto; Ramadi, Ramadi; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that the lack of jumps from athletes in punches and drafts makes it easy for opponents to get points, and not maximum when athletes jump, so when making a ball is often involved on the net and damaging the ball often does not hit the ball so that the opponent easily hits the ball defeat it. This type of research is a type of experimental study to see the effect of exercise and the purpose of this study was to look at the effect of barrier hop training on leg muscle strength in the SMAN 1 Sungai Mandau volleyball team. The population in this research was the Bolavoli team of SMAN 1 Sungai Mandau with a total of 10 people. The sampling technique is the use of total sampling, where the total population is sampled. Data collection techniques were obtained from the pre-test and the post-test. The instrument in this research used vertical jump as an aid to measure leg muscle strength. The data is then processed statistically to test normality using the liliefors test at a significant level of 0.05 α. Based on the analysis of the normality of the data X, it produces a LoMax of 0.119 and an Ltable of 0.258, which means LoMax <Ltable. while variable Y yields LoMax of 0.141 and Ltable of 0.258. This means LoMax <L table. The analysis was performed with a t-test. Based on data analysis and discussion, it can be concluded that there is an effect of barrier hop training on leg muscle strength on the SMAN 1 Sungai Mandau volleyball team of the River, as shown by Thitung of 3,167 and Ttable 1,833. Means Thitung> Ttable At the level ɑ = 0.05.Key Words: Barier Hop Exercise, Leg Muscle Strength